Cyclic Axial Compression Behavior of FRP-Confined Seawater Sea-Sand Concrete-Filled Stainless Steel Tube Stub Columns - Zeng, Jun-Jie; Liao, JinJing; Liang, Wen-Feng; Guo, Yong-Chang; Zhou, Jie-Kai; Lin, Jia-Xiang; Yan, Kang (Frontiers in Materials, 2022)
Concrete-filled steel tube (CFST) columns have been widely used in onshore constructions. To extend its applications to coastal/offshore structures and meanwhile relieve the overexploitation on freshwater and river-sand, an FRP-confined seawater sea-sand concrete-filled stainless steel tube (F-SSCFSST) column is proposed. The cyclic axial compressive behavior of this newly proposed column was investigated in this study. A total of 22 specimens (including nine pairs of specimens for cyclic compression and four individual specimens for monotonic compression) were tested. Most importantly, the influences three loading patterns (i.e., single full unloading/reloading, repeated full unloading/reloading, and mixed of repeated full and partial unloading/reloading) were studied. The results showed that, although all F-SSCFSST specimens failed from FRP rupture in the mid-height area, the FRP rupture was less fierce for specimens with repeated internal unloading/reloading cycles. Similar to FRP-confined concrete, the envelop curve of cyclic aixal load-strain response matched closely with the monotonic compression curve for a particular specimen. However, the unloading curve was less curly compared with that of a typical FRP-confined concrete. The confinement effect provided by the FRP jacket was much stronger than that by the stainless steel tube. Although Lam and Teng’s model which is proposed for FRP-confined concrete could provide satisfactory estimations for strain recovery ratios and stress deterioration ratios, it underestimated the envelop plastic strains by 20%.